2021
DOI: 10.1016/j.celrep.2021.109301
|View full text |Cite
|
Sign up to set email alerts
|

A critical role of hepatic GABA in the metabolic dysfunction and hyperphagia of obesity

Abstract: Geisler et al. show that GABAtransaminase catalyzes GABA synthesis in the liver of obese mice, resulting in hyperinsulinemia, insulin resistance, and hyperphagia. In people with obesity, liver GABA-transaminase expression is positively associated with hyperinsulinemia. Thus, GABAtransaminase inhibitors may be effective at restoring glucose homeostasis in obese, hyperinsulinemic, insulinresistant individuals.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 53 publications
(66 reference statements)
3
11
0
Order By: Relevance
“…In this context, it should be noted that GABA, the natural ligand of GABA A R, has been implicated in obesogenic pathways outside of the nervous system. Thus, hepatic synthesis of GABA, catalyzed by GABA-transaminase, is upregulated in obese mice and persons, and its inhibition improves both hyperphagy and diabetes in mice [ 59 ]. GABA is also increased in the interscapular BAT of obese mice, and its oral supplementation with the drinking water suffices to worsen glucose intolerance in the context of HFD [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this context, it should be noted that GABA, the natural ligand of GABA A R, has been implicated in obesogenic pathways outside of the nervous system. Thus, hepatic synthesis of GABA, catalyzed by GABA-transaminase, is upregulated in obese mice and persons, and its inhibition improves both hyperphagy and diabetes in mice [ 59 ]. GABA is also increased in the interscapular BAT of obese mice, and its oral supplementation with the drinking water suffices to worsen glucose intolerance in the context of HFD [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Damage to liver cells results in increased permeability of cell membranes, which leads to the entry of AST and ALT from the liver into the bloodstream. 20 The HFD triggered high ALT levels in the blood ( p < 0.05) while no significant effect was observed for the AST level ( p > 0.05). Notably, LJ, FLJ and GABA supplementation could effectively reduce the ALT levels.…”
Section: Resultsmentioning
confidence: 89%
“…Geisler et al found that hepatocyte GABA production (GABAtransaminase catalyzed synthesis) effectively regulates glucose regulation dysfunction and feeding behavior associated with obesity. 20 Moreover, previous studies have shown that oral treatment with GABA reduced the body weight gain, epididymal fat mass, and adipocyte size of HFD-fed mice, mainly due to the action of GABA on the peripheral GABA receptors, which inhibited insulin resistance and obesity by inhibiting obesityrelated inflammation and up-regulating Treg responses in vivo. 47 In addition, it can be seen in Fig.…”
Section: Gaba Attenuates Obesity Via Regulating Intestinal Flora In Micementioning
confidence: 99%
“…Glutaminase and glutamate decarboxylase play an important role in GABA synthesis, and hepatic synthesis of GABA, catalyzed by GAD, is upregulated in obese mice. Hepatic GAD inhibition and knockdown decreased basal hyperinsulinemia and hyperglycemia and improved glucose intolerance, as well as playing a positive role in improving NASH (Geisler et al, 2021). The results showed that AB23A could down‐regulate the expression of Gls and Gad1 mRNA and reduce blood ammonia levels.…”
Section: Discussionmentioning
confidence: 99%